Teachers’ Perceptions on Content in the Implementation of Islamic Religious Education Competency-based Curriculum in Secondary Schools of Wakiso District - Uganda - Sserwadda, Batiibwe Moses; Kiggundu, Musoke Muhammad; Mugagga Anthony Muwagga (East African Journal of Education Studies, 2024)
The current study explored teachers’ perceptions on implementing content of IRE in a competence-based curriculum in selected secondary schools in Wakiso District. It was based on a phenomenological design, with teachers as the unit analysis. The sample size depended on the saturation of the findings acquired. Teachers were sampled using simple random sampling while participants in other categories were purposively selected. Interview guides and focus group discussion guides were used as data collection instruments. Data was analysed using the thematic analysis method. Results revealed that IRE teachers had perceived the content of IRE CBC as being implemented effectively to bring compliance to the 21st-century competencies involved. It was concluded that IRE teachers in Wakiso District had perceived IRE Competency-based content taught as valid, relevant and aligned to educational goals and learners’ needs. Also, the teachers perceived this curriculum in a way that it was addressing the contemporary needs of the society, and it was worthy to be implemented. It was recommended that if the IRE Competency-based Curriculum was to be effectively implemented in the selected secondary schools in Wakiso District, relevant stakeholders at Wakiso District Education Department, Ministry of Education and Sports officials, UNEB officials and NCDC Officials should organize seminars, workshops and sensitization conferences to equip teachers with the necessary skills to handle IRE Competency-based curriculum